2018
DOI: 10.1161/circulationaha.117.028833
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial Adipose Tissue Regulates Granulopoiesis, Fibrosis, and Cardiac Function After Myocardial Infarction

Abstract: Our findings unveil a new mechanism by which the pericardial AT coordinates immune cell activation, granulopoiesis, and outcome after MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
145
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(152 citation statements)
references
References 34 publications
6
145
0
1
Order By: Relevance
“…Therefore, in addition to the differences in myeloid cell recruitment described herein, differences in the number of CD4 + T cells present in a mouse strain may influence Th1/Th2 polarization and potentially cardiac remodelling post-MI [36]. Horckman et al have recently shown that removal of pericardial adipose tissue is associated with an almost 50% reduction in recruitment of neutrophils to the myocardium following MI [26]. Findings from the present study, showing that peak neutrophil infiltration of pericardial adipose tissue precedes the peak of infarct zone neutrophil count, supports the involvement of pericardial adipose tissue in regulating the infarct zone inflammatory response.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Therefore, in addition to the differences in myeloid cell recruitment described herein, differences in the number of CD4 + T cells present in a mouse strain may influence Th1/Th2 polarization and potentially cardiac remodelling post-MI [36]. Horckman et al have recently shown that removal of pericardial adipose tissue is associated with an almost 50% reduction in recruitment of neutrophils to the myocardium following MI [26]. Findings from the present study, showing that peak neutrophil infiltration of pericardial adipose tissue precedes the peak of infarct zone neutrophil count, supports the involvement of pericardial adipose tissue in regulating the infarct zone inflammatory response.…”
Section: Discussionmentioning
confidence: 85%
“…Recently it has been demonstrated that pericardial adipose tissue regulates the innate immune response in the infarcted myocardium [26]. Similar to the infarct zone, neutrophils were the predominant myeloid cell type infiltrating the pericardial adipose tissue of both C57BL/6 and BALB/c mice during the early inflammatory phase, but peaked earlier at day 1 post-MI (Fig.…”
Section: C57bl/6 Mice Show An Enhanced Inflammatory Response In the Rmentioning
confidence: 83%
See 1 more Smart Citation
“…5,9 Recent work in mice by Horckmans et al demonstrated a strong correlation between pericardial FALC B cell activation, the extent of cardiac inflammation and functional outcomes following MI. 11 Using cannabinoid receptor CB2 deficient mice (CB2 -/-) which have increased levels of circulating B cells, they concluded that secretion of Granulocyte-macrophage colony-stimulating factor (GM-CSF) by pericardial B cells promotes bone marrow granulopoiesis, cardiac neutrophil infiltration, enhances fibrosis and worsens functional cardiac outcome. 11 Furthermore, pericardial cavity macrophages have a functional phenotype comparable to other F4/80 hi serous cavity macrophage populations and are controlled by the expression of the transcription factor GATA-6.…”
Section: Introductionmentioning
confidence: 99%
“…11 Using cannabinoid receptor CB2 deficient mice (CB2 -/-) which have increased levels of circulating B cells, they concluded that secretion of Granulocyte-macrophage colony-stimulating factor (GM-CSF) by pericardial B cells promotes bone marrow granulopoiesis, cardiac neutrophil infiltration, enhances fibrosis and worsens functional cardiac outcome. 11 Furthermore, pericardial cavity macrophages have a functional phenotype comparable to other F4/80 hi serous cavity macrophage populations and are controlled by the expression of the transcription factor GATA-6. [12][13][14] Deniset et al have shown that these macrophages relocate to the injured heart where they act to suppress cardiac fibrosis.…”
Section: Introductionmentioning
confidence: 99%